Mediating Sustainability and Liveability—Turning Points of Green Space Supply in European Cities - Wolff, Manuel; Haase, Dagmar (Frontiers in Environmental Science, 2019)
Urban growth in and around European cities affects multiple aspects of the environment including green spaces. On the one hand, many cities struggle with environmental problems, overcrowding and overuse resulting from high population densities. On the other hand, high densities result in better access to public green spaces, effective public transport, or less demand for resources. Consequently, finding a balance between density and high liveability in a green and sustainable urban environment is a major challenge for urban planning. Although many studies effectively report and discuss the provision of green spaces in European cities, they lack a systematic answer to what extent the provision of green spaces meets the potential population demand, and to what extent the differences can be detected between types of green. Against this background, this paper develops a systematic understanding of green space supply and its relation to the residential density of cities. In so doing, it detects turning points of green space supply in 905 European cities. The results show that green space supply is sensitive to the type of green space, population size and location of cities. While the supply for total green spaces is constantly decreasing with increasing residential density, the relation between residential density and the supply of urban green indicates turning points. At a certain residential density cities have a high potential to optimise the balance between sustainability and liveability. However, there is no single optimal residential density. Rather, with increasing residential density the green space supply is decreasing and cities need to define different qualities for differently dense neighbourhoods accounting for their specific character and their location within the urban continuum. As for most of the European cities a decrease of urban population or built-up area in the future cannot be expected. By systematically understanding the linkages between green spaces in cities and residential densities, this paper uncovers densities that indicate a turning point of green space supply, which can be used as a comparative instrument in order to respond to the growing need for better green space management planning in areas of high residential density.